[Letter to R. Gephardt from A. J. Stevens] - ARTHUR J. STEVENS (Tufts Archival Research Center, 2007)
Letter from Arthur J Stevens to Rep. Richard A. Gephardt regarding cigarette excise taxes. Thanks Gephardt for the opportunity for Stevens to share his opinion. States that excise taxes are the most regressive of all taxes, and asks Gephardt to remember this.